The Effect of Using Bingo Game on Students’ Vocabulary Mastery of The X Grade at Mas Al Washliyah 21 Firdaus - Fitri, Sari aulia; Sihite, Meida Rabia; Harahap, Yunita Mutiara (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
The purpose of this study is to determine whether playing bingo has a meaningful impact on vocabulary mastery. Experimental research design was the method used in this study. For the academic year 2023–2024, class X students at MAS Alwasliyah 21 Firdaus were the subjects of this study. There were two X grade classrooms. Every class has twenty pupils in it. Thus, there are 40 pupils in total. Class X-2 was chosen as the control group, and Class X-1 as the experimental group. It is known that the t-test was used for data analysis after the data were computed using SPSS. Following the computation of the data, it is known that, at a significance level of α = 0.05, the t count value (11,374) is greater than the t table value (1,68) with degrees of freedom (df = 38). This suggests that the Null Hypothesis (H0) was successfully rejected and the Alternative Hypothesis (Ha) was successfully accepted. Consequently, the usage of bingo games has a big impact on students' knowledge of the material.